Analysis of the spatial data automatic classification methods in the geoinformatic systems - Roik, O. M.; Tabachnyk, Yu. Ya. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The spatial data automatic classification methods are analyzed, and their pros and cons are given. It is shown, what exactly methods are reasonable to use in the spatial data classification task from the computational complexity and availability for the both attributive and geographical data analysis point of view.